MENUMBUHKAN KASIH SAYANG DAN HUBUNGAN POSITIF DI SEKOLAH DAN LINGKUNGAN SEKITAR - Adelia Citra Erlansyah; Nurul Janah; Putri Fairuz; Salsabilla Citra Dwi Rahmadani; Zahwa Kania Putri (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to examine the role of compassion and positive social interactions in enhancing students’ mental well-being within the school setting. The background highlights the importance of shaping adolescents into empathetic, supportive individuals who are emotionally resilient by fostering compassion both toward themselves (self-compassion) and others. The intervention took the form of a psychoeducational session for 8th and 9th grade students at SMPN 11 Tambun Selatan, utilizing pre-tests and post-tests to assess student understanding before and after the material was delivered. The results demonstrated a significant improvement in students’ comprehension, including their conceptual understanding, awareness of psychological benefits, and the application of compassion and positive relationships in daily life. Students also showed greater awareness of the importance of mutual respect, emotional support, and healthy communication. The psychoeducation proved to be an effective approach for deepening students’ understanding and shows potential as a mental health intervention model for adolescents in school environments. Overall, strengthening the values of compassion and healthy social relationships plays a crucial role in creating a supportive learning environment that fosters students' psychological development.